Endoscopic lung volume reduction with one-way valves in patients with severe chronic obstructive pulmonary disease with hypercapnia - Lenga, Pavlina; Grah, Christian; Ruwwe-Glösenkamp, Christoph; Saccomanno, Jacopo; Rückert, Jens; Eggeling, Stephan; Gläser, Sven; Kurz, Sylke; Eisenmann, Stephan; Krüger, Marcus; Schmidt, Bernd; Schneider, Paul; et al. (Respiration, 2022)
Background: Robust clinical evidence on the efficacy and safety of endoscopic lung volume reduction (ELVR) with one-way valves in patients with severe lung emphysema with chronic hypercapnic respiratory failure is lacking. Objective: The aim of this study was to compare patient characteristics, clinical outcome measures, and incidences of adverse events between patients with severe COPD undergoing ELVR with one-way valves and with either a partial pressure of carbon dioxide (pCO2) of ≤45 mm Hg or with pCO2 >45 mm Hg. Methods: This was a multicentre prospective study of patients with severe lung disease who were evaluated based on lung function, exercise capacity (6-min walk test [6-MWT]), and quality-of-life tests. Results: Patients with pCO2 ≤45 mm Hg (n = 157) and pCO2 >45 mm Hg (n = 40) showed similar baseline characteristics. Patients with pCO2 ≤45 mm Hg demonstrated a significant increase in forced expiratory volume in 1 s (p < 0.001), a significant decrease in residual volume (RV) (p < 0.001), and significant improvements in the quality of life and 6-MWT at the 3-month follow-up. Patients with pCO2 >45 mm Hg had significant improvements in RV only (p < 0.05). There was a significant decrease in pCO2 between baseline and follow-up in hypercapnic patients, relative to the decrease in patients with pCO2 ≤45 mm Hg (p = 0.008). Patients who were more hypercapnic at baseline showed a greater reduction in pCO2 after valve placement (r = −0.38, p < 0.001). Pneumothorax was the most common adverse event in both groups. Conclusions: ELVR with one-way valves seems clinically beneficial with a remarkably good safety profile for patients with chronic hypercapnic respiratory failure.